(untitled) (Perner’s Contacts, 2015)
This article deals about modified way of switch area capacity assessment in a railway station and about the software tool that realize the calculation. The procedure of calculation originates from the leaflet UIC 406. Original methodology that is described in the leaflet is based on the knowledge of a switch area (only some parts of it) exclusion times because of occupancy by individual trains. In some cases it might be problem to get input data in needed format. There are some simulation tools that provide occupancy times it different format and to convert the data to a needed format is not easy to do. Due to this reason there was designed alternative way how to assess capacity of switch area that use data from simulation tools. To assess the capacity there was developed software tool that follow rules from the leaflet UIC 406 so the results that it provides are equal to original methodology.